Misperceptions of the Halal Certification Policy: Challenges of Micro, Small and Medium Enterprises Development - Bahari, Raha; Ardliansyah, Moelki Fahmi; Murdiana, Elfa (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2024)
This research discusses the understanding of business actors toward halal certification policies and halal production processes, which are often considered less important. This is a major challenge in developing micro, small, and medium enterprises (MSMEs). The research focus includes three aspects: (1) how MSME actors perceive the halal certification policy; (2) how they view the halal concept in the production process; and (3) strategic steps to overcome these misperceptions. This research uses a qualitative approach with purposive sampling to select informants based on certain criteria. Data were collected through a narrative approach, which aims to explore individual experiences related to halal certification policies. The results show that in-depth education on the importance of halal certification, both as a legal obligation and a strategy to increase competitiveness, is needed. A more inclusive and participatory approach in policy formulation can increase the involvement and understanding of MSMEs. Thus, education, technical support, and simplification of certification procedures are expected to help MSMEs undergo the halal certification process more confidently. To improve product quality, expand market access, and strengthen competitiveness sustainably.